Utilization of Bacillus subtilis Culture for Fermentation of Arabica Coffee (Coffea arabica) from Toraja Regency - Asdar, Asdar; Patang, Patang; Sukainah, Andi (Journal of Agroscience Indonesia, 2023)
The aim of this research was to determine the effect of giving Bacillus subtilis concentrations on caffeine levels and the physicochemistry of Arabica coffee beans. This study used a Complete Randomized Design (RAL) where the concentration of B. subtilis was 0%, 1%, 2%, 3%, 4%, 5%. Variables observed in this study included total plate numbers (ALT), total titrated acid (TAT) and pH, as well as arabica coffee bean tests (water and caffeine content). The results of this study show that B. subtilis affects ALT, TAT, pH, water content and caffeine content of fermented liquid in arabica coffee beans. The lowest caffeine content of arabica coffee beans is made from arabica coffee beans added 5% B. subtilis during fermentation with a caffeine content of 1.34%.